2021
DOI: 10.1371/journal.pone.0233821
|View full text |Cite
|
Sign up to set email alerts
|

Validation of suitable genes for normalization of diurnal gene expression studies in Chenopodium quinoa

Abstract: Quinoa depicts high nutritional quality and abiotic stress resistance, attracting strong interest in the last years. To unravel the function of candidate genes for agronomically relevant traits, studying their transcriptional activities by RT-qPCR is an important experimental approach. The accuracy of such experiments strongly depends on precise data normalization. To date, validation of potential candidate genes for normalization of diurnal expression studies has not been performed in C. quinoa. We selected e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…As reference genes, we used the geometric mean of CqIDH ‐ A and CqPTB genes. These genes turned out to be best suited as reference genes because they were stably expressed during different growth stages and different time points of the day (Maldonado‐Taipe, Sarange, Schmöckel, Jung, & Emrani, 2021).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As reference genes, we used the geometric mean of CqIDH ‐ A and CqPTB genes. These genes turned out to be best suited as reference genes because they were stably expressed during different growth stages and different time points of the day (Maldonado‐Taipe, Sarange, Schmöckel, Jung, & Emrani, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…We mapped Illumina short-read sequences against an improved version of the quinoa reference genome (Jarvis et al, 2017). SNP variants were identified on a population scale using the '-emitRefConfidence' function of the HaplotypeCaller algorithm on each sample, followed by joint genotyping on all samples using GenotypeGVCFs from the Genome Analysis Toolkit (McKenna et al, 2010). The resulting VCF file was further filtered based on minor allele frequency (MAF) ≥ 0.05, minimum mean depth (min-meanDP) ≥ 5.0, and maximum-missing (max-missing) ≤ 0.5 using VCFtools (Danecek et al, 2011) and obtained a high confident SNP data set (HC-SNPs).…”
Section: Dna Sequencing and Haplotype Analysismentioning
confidence: 99%
“…Among them, 18S , GTP , IDH and CYP and their combinations were the most stable endogenous reference genes (Table 4 ). Several genes have been shown to be good stable samples, including 18S 53 , 54 , IDH 55 , 56 , and CYP 57 , 58 . In addition, the experimental results showed that GTP can be used as a stable results which is contrary to Zhao’s results 41 ; GAPDH and α-TUB were the least stable genes under various stresses in the present experimental catch, but were the most stable reference in some reported endogenous reference gene studies 59 61 , which is an indication that differences in species or experimental conditions lead to uniqueness of genes, therefore, the selection of suitable samples under different stress conditions is necessary to achieve reliable experimental results.…”
Section: Discussionmentioning
confidence: 99%
“…Primers used for gene expression analysis are listed in Supplementary Table 2. CqPTB and CqIDH-A, identified in our previous study as suitable housekeeping genes for RT-qPCR analysis in quinoa, were used as reference genes (Maldonado-Taipe et al ., 2021).…”
Section: Methodsmentioning
confidence: 99%